Предмет: Алгебра,
автор: RMyr
Упростите выражение:
a) a(b + 3) + b(a + 3) – 3(a + b);
б) 2(х - у) + 6(у – x) – (4х – 4у);
в) a(b + c) – b(a + с) – с(a + b);
г) m(n – l) + n(I – m) + l(m — n).
Ответы
Автор ответа:
1
a) =ab+3a+ab+3b-3a-3b=2ab
б) =2x-2y+6y+6x-4x+4y=-8x+8y=-8(x-y)
в) =ab+ac-ab-bc-ac-bc=-2bc
г) =mn-ml+nl-mn+lm-nl=0
Объяснение:
Там просто треба було розкрити дужки, порахувати, скоротити)))
Похожие вопросы
Предмет: Математика,
автор: danuloparulyk
Предмет: Другие предметы,
автор: darynabas81
Предмет: Английский язык,
автор: rofylys
Предмет: История,
автор: jenjamingaleeva
Предмет: Математика,
автор: nikryazanov01